Application of Azospirillum brasilense Lipopolysaccharides to Promote Early Wheat Plant Growth and Analysis of Related Biochemical Responses - Hernaández-Esquivel, Alma Alejandra; Castro-Mercado, Elda; Valencia-Cantero, Eduardo; Alexandre, Gladys; García-Pineda, Ernesto (Frontiers in Sustainable Food Systems, 2020)
While the effects of lipopolysaccharides (LPS) of plant pathogenic bacteria in induction of plant defense responses have been characterized, the role of LPS of beneficial rhizobacteria on plant growth is less clear. In this study, we assessed the in vitro effects of LPS from the rhizobacterium Azospirillum brasilense Sp245 on early growth of wheat seedlings (Triticum aestivum) and on some biochemical responses related to growth, like peroxidase (POD) enzyme activity and Ca2+ availability. Four days after treating the seedlings with various concentrations of A. brasilense LPS (10 to 1000 µg/mL), the growth of the seedlings was enhanced as evidenced by significant increase in leaf and root lengths as well as fresh weight. These increases were comparable to those resulting from inoculation with the rhizobacteria. POD enzyme activity increased significantly in roots treated with LPS and was concentration dependent. Salicylhydroxamic acid, an inhibitor of peroxidase activity, decreased POD activity and plant growth promoted by LPS. Lanthanum, an inhibitor of calcium channels, and EGTA, inhibited plant growth and POD activity promoted by LPS, while the calcium ionophore A23187 alone was able to increase plant growth and POD activity. In summary, the results suggest that isolated LPS of A. brasilense have the capacity to promote early wheat seedling growth and that POD enzyme activity and Ca2+ levels are involved in the LPS-mediated biological activity.